Pemanfaatan Teknologi Informasi dalam Pendidikan dan Pembelajaran di Era Revolusi Industri 4.0 - Mortigor Afrizal Purba; Agus Defri Yando (Prosiding, 2020)
AbstractThis study aims to describe the education and learning challenges based on information technology in the Industrial Revolution 4.0 Era and Indonesia's readiness to answer the challenges of education in the era of the industrial revolution 4.0 in building an information technology-based learning system. In Indonesia, readiness to face the challenges of education in the era of the industrial revolution 4.0 is to immediately improve the capabilities and skills of human resources through education by producing reliable operators and analysts in the field of education management as a driver for advancing information technology-based education in Indonesia to answer the challenges of Industry 4.0 which continues to advance rapidly. Education management policies in Indonesia currently encourage all levels of education, especially higher education to take advantage of advances in digital technology and educational computing in the era of the fourth industrial revolution. Some solutions that can be done include the suitability of curricula and policies in education, the readiness of human resources in utilizing ICT, optimizing the abilities of students, and developing the character of students, and the readiness of digital-based learning facilities and infrastructure.